2022
DOI: 10.1155/2022/3843954
|View full text |Cite|
|
Sign up to set email alerts
|

Bioinformatic Analysis and Cellular Assays Identify Substance P Influencing Th17/Treg Differentiation via the MyD88 Pathway as a Potential Contributor to the Progression of Asthma and Allergic Rhinitis

Abstract: Objective. This study is aimed at investigating the role of substance P (SP) in the development of asthma. Methods. The Gene Expression Omnibus (GEO) database was used to characterize SP expression in allergic rhinitis (AR) and asthma. Peripheral blood was collected from patients with asthma or AR. The expression of relevant cytokines and neuropeptides was measured. Enzyme-linked immunosorbent assay (ELISA) was also performed. The mast cell line LAD2 and the lung bronchial epithelial cell line BEAS-2B were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Therefore, an in-depth investigation into the pathogenesis of AR is urgent for the prevention and treatment of AR. More and more evidences have found that the pathogenesis of AR is not only caused by a simple immune disorder but is also regulated by neuronal signaling, such as substance P [33], neurokinin [34], vasoactive intestinal peptide [35], and calcitonin-related gene peptides [36]. Therefore, AR has also been described as an immune-neuronal disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an in-depth investigation into the pathogenesis of AR is urgent for the prevention and treatment of AR. More and more evidences have found that the pathogenesis of AR is not only caused by a simple immune disorder but is also regulated by neuronal signaling, such as substance P [33], neurokinin [34], vasoactive intestinal peptide [35], and calcitonin-related gene peptides [36]. Therefore, AR has also been described as an immune-neuronal disorder.…”
Section: Discussionmentioning
confidence: 99%
“…TRIzol (Sangon, Shanghai, China) was used to obtain RNA from the osteoblast cell line and ovarian granulosa cell line treated above according to the manufacturer’s instructions as previous researches ( Rio et al, 2010 ; Ma et al, 2022 ; Xuan et al, 2022 ). The obtained RNA was reverse transcribed into cDNA using GoScript ™ Reverse Transcription Kit (Promega, Madison, WI, SA), and the mRNA expression level was subsequently determined using FastFire qPCR PreMix (SYBR Green) (Tiangen, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, exploration of AR based on GSE75011 and GSE46171 has mainly targeted key genes differentially expressed between AR and control samples [39][40][41][42]. In the current study, the biological signi cance of lipid metabolism in AR was rst systematically explored at the genetic level through these datasets.…”
Section: Comparisons With Other Studies and Contribution Of The Curre...mentioning
confidence: 99%